A case of peripheral ulcerative keratitis associated with limited granulomatosis polyangiitis - Anushree Gupta; Shruti Anand (Journal of Clinical Ophthalmology and Research, 2020)
A 28-year-old Indian female presented with sudden onset reduced vision and pain in the left eye following blunt trauma. There was chronic history of redness, tearing, and irritation in both the eyes. She was diagnosed with peripheral ulcerative keratitis and corneal perforation in the left eye. Her corneal perforation was repaired with direct closure. Diagnostic workup revealed limited granulomatosis polyangiitis. The patient was treated with topical and systemic steroids and immunosuppressant drugs (rituximab).